1987
DOI: 10.1161/01.res.61.3.372
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-promoting phorbol esters inhibit cardiac functions and induce redistribution of protein kinase C in perfused beating rat heart.

Abstract: Activation of protein kinase C has been implicated in the regulation of a variety of cellular reactions. Although we, and others, have found protein kinase C and its substrate proteins to be present in both membrane and cytosolic fractions in the heart, the physiologic role of this kinase in the regulation of cardiac functions remains unknown. In the present study, we found that in isolated perfused rat heart, administration of phorbol esters 4/3-phorbol 12,13-dibutyrate(PDBu) and 12-0-tetradecanoylphorbol 13-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(42 citation statements)
references
References 36 publications
7
35
0
Order By: Relevance
“…8). These findings are consistent with many previous studies that demonstrated that phorbol ester and synthetic diacylglycerol, and also ␣-adrenergic agonists and angiotensin II under certain conditions, exert significant depressive effects on the contractile function in a variety of cardiac preparations (33)(34)(35)(36)(37) and reduce diastolic [Ca 2ϩ ] i as well as Ca 2ϩ transient peaks in isolated perfused heart (36) and isolated adult cardiomyocytes (35,37). Since phorbol ester and exogenous diacylglycerol do not enhance phosphorylation of phospholamban in the sarcoplasmic reticulum in intact cardiomyocytes (38,39), increased Ca 2ϩ extrusion across the sarcolemma is the most likely mechanism for the observed decrease in [Ca 2ϩ ] i .…”
Section: Discussionsupporting
confidence: 92%
“…8). These findings are consistent with many previous studies that demonstrated that phorbol ester and synthetic diacylglycerol, and also ␣-adrenergic agonists and angiotensin II under certain conditions, exert significant depressive effects on the contractile function in a variety of cardiac preparations (33)(34)(35)(36)(37) and reduce diastolic [Ca 2ϩ ] i as well as Ca 2ϩ transient peaks in isolated perfused heart (36) and isolated adult cardiomyocytes (35,37). Since phorbol ester and exogenous diacylglycerol do not enhance phosphorylation of phospholamban in the sarcoplasmic reticulum in intact cardiomyocytes (38,39), increased Ca 2ϩ extrusion across the sarcolemma is the most likely mechanism for the observed decrease in [Ca 2ϩ ] i .…”
Section: Discussionsupporting
confidence: 92%
“…The latter were more pronounced at + 40 mV than at -80 mV, and were usually not reversed by 5-10 min washouts with control solution, a difficulty previously reported in regard to other cardiac effects of phorbol esters (e.g. Yuan et al, 1987;Tseng & Boyden, 1991). However, stimulations produced by shorter treatments with moderate concentrations of PMA were reversible on occasion (see Figure 5).…”
Section: Drugsmentioning
confidence: 57%
“…Inhibition by PDBu of the agonist-induced phosphoinositide hydrolysis and functional changes have been demonstrated in a variety of cells, including smooth muscle cells (Brock et al, 1985), platelets (Kagaya et al, 1990) and myocardial cells (Yuan et al, 1987). In addition, in chick embryo myocytes, PDBu decreased Ca2+ transients increased by All and PMA inhibited the Allmediated increase in Ca2l transients in rat myocytes (Kem et al, 1991).…”
Section: [ §X Y'mentioning
confidence: 99%